Changes in the Described Elements of Sensoji Temple following its Park Designation - Ito, Hiromu (Advances in Social Sciences Research Journal, 2020)
How the elements of a religious facility became recognized after its designation as a park was clarified in this study based on the changes in the descriptions of the facility in guidebooks and pictorial charts. Immediately after the facility was designated as a park, the image of a park was merely added to the idea of the temple. However, Kinryusan Sensoji Temple clearly became considered one of the park components only after the full-scale maintenance and division of the park in 1884. These changes were greatly influenced by the changes in the physical environment based on the institutional meaning of the park in addition to the background of the existence and use of the park becoming widely established from the period when it was designated as a park to the period when it was developed into a tourist attraction. While the extent of recognition of Sensoji Temple as a park increased, the extent of recognition of the site as a temple diminished and became limited. Tourists perceived that Sensoji Temple was composed only of Kannondo Hall and spatially considered the entire park as a collection of sections. As a result, the area recognized as a temple was limited to the central part of the Sensoji Temple precinct, while the spatial functions that Sensoji Temple originally possessed were divided and removed. Thus, the characteristics of the temple as a tourist site also changed.